Manažment ošetrovateľskej starostlivosti o onkologického pacienta s konfliktom v rozhodovaní - Slamková, Alica; Boledovičová, Mária (Ošetrovateľstvo, 2012)
Aim: Development and use of standard terminology by nursing classification systems is one of the characteristics of the nursing profession in the 21st century. The objective of the application is precise definition and formulation of the activities performed by nurses related to the needs of patients for achievement of specific outcomes. In this paper we focus on the issues of care for oncologic patients in which the decisional conflict developed in relation to health care. We emphasise the priority role of nurses in solving the nursing diagnosis Decisional Conflict (specify) 00083, including assisting patients and their families in decision making. It is important for nurses to be able to empathize with the current status of the patient, and work using the method of nursing process which provides a fixed procedure. Methods: The methods of intervention study and content analysis were used. Mathematic and statistical methods: the Student’s t-test for two dependent samples was used in the NOC (Nursing Outcomes Classification) level. The research was performed from 2007 to 2009 in the Teaching Hospital in Nitra and the St. Svorad΄s Specialist Hospital Zobor in Nitra. Results: The results of the research show the positive effects of the use of the chosen sets of nursing classification systems NIC (Nursing Interventions Classification) and NOC (Nursing Outcomes Classification) in decision making of oncologic patients. There are significant differences between the intervention and control groups in the performed nursing activities of the chosen set of the NIC, in terms of the lower number of performed activities in the control group. There are significant differences in comparison of the values of the indicators of the chosen NOC set between the entry and secondary measurements, in terms of reaching a decision by patients and meeting the goals.
Keywords: nejistota; ošetřovatelské zhodnocení; Nurse's Role; Uncertainty; Nursing Assessment; Communication; Humans; Nursing Diagnosis; Medical Oncology; rozhodování; Nursing Research; komunikace; Inpatients; Hospital Departments; ošetřovatelská péče; Statistics as Topic; hospitalizovaní pacienti; lékařská onkologie; ošetřovatelský výzkum; ošetřovatelská diagnóza; statistika jako téma; nemocniční oddělení; Decision Making; lidé; Nursing Care; role ošetřovatelky